Faithful Finance: Unlocking Banking Islamization in Afghanistan - Mustafa Disli; Ahmad Khalid Hatam; Shakir Jalaly (Economies, 2023)
This paper explores the challenges and prospects associated with the adoption of Islamic banking in Afghanistan. Despite the global growth and acceptance of Islamic banking by approximately 50 countries by 1997, Afghanistan only embraced it between 2008–2009. The decision to convert conventional banks to Islamic ones, driven by the involvement of interest rates (riba) in the prevailing system, necessitates a thorough examination of the challenges and the need for an appropriate response. The study employs qualitative, analytical, and exploratory methods, reviewing secondary sources and conducting unstructured interviews with key stakeholders, including officials from the Da Afghanistan Bank (DAB), staff of Islamic banking institutions, experts in Islamic banking and finance, and consumers. The findings reveal that the challenges in promoting Islamic banking in Afghanistan are more complex and multi-layered than commonly understood, stemming from the legal system, regulatory capacities and mindset, banking services, and public perception. The paper emphasizes the importance of addressing these challenges comprehensively to safeguard the already fragile economic and financial sector. Failure to do so may lead to further deterioration. This research contributes to the existing body of knowledge by shedding light on the unique challenges and prospects of Islamic banking in Afghanistan, providing valuable insights for policymakers, regulators, and practitioners in shaping an effective transformation strategy.